Typology and factors underlying criminals’ utilisation of spiritual charms for crime perpetration in Nigeria - Ojedokun, Usman Adekunle (Crime, law and social change, 2025)
Despite the fact that spiritual charms are widely recognised as a major component among the objects that criminals in Nigeria frequently rely upon for crime perpetration, research focusing on this phenomenon is very scarce. Therefore, this paper attempted to fill this lacuna by examining the types and patterns of spiritual charms usage for criminal activities in Nigeria. Relying on the propositions of symbolic interactionism theory as the conceptual framework, it examined the factors underlying criminals’ utilisation of spiritual charms for crime perpetration, the types of crimes for which criminals commonly deploy spiritual charms, and the implications which criminals’ use of spiritual charms holds for crime prevention and control. The paper argued that the availability of a wide variety of spiritual charms in Nigeria poses a unique challenge to criminal justice officials because access to them plays a critical role in gravitating many individuals towards criminality.